Islam and the Americas - Khan, Aisha (New world diasporas, 2015)
This volume edited by Aisha Khan explores Muslims' lived experiences in the Western Hemisphere and the ways in which Islam has been codified in the New World by "Muslim minority" societies, using disparate case studies from the Caribbean, Suriname, Brazil, Mexico, and others in the Atlantic World